2021
DOI: 10.1016/j.gendis.2019.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo Tumor Suppressor Pathway (YAP/TAZ/TEAD/MST/LATS) and EGFR-RAS-RAF-MEK in cancer metastasis

Abstract: Hippo Tumor Suppressor Pathway is the main pathway for cell growth that regulates tissue enlargement and organ size by limiting cell growth. This pathway is activated in response to cell cycle arrest signals (cell polarity, transduction, and DNA damage) and limited by growth factors or mitogens associated with EGF and LPA. The major pathway consists of the central kinase of Ste20 MAPK ( Saccharomyces cerevisiae ), Hpo ( Drosophila melanogaster ) or MST kinases (mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 185 publications
0
22
0
Order By: Relevance
“… 100 Eventually, IkBδ is derived from the p100 fragment containing ankyrin, which generates negative feedback on the main NF-kB signaling. 101 , 102 …”
Section: Nf-kb Secondary Activation Pathwaymentioning
confidence: 99%
“… 100 Eventually, IkBδ is derived from the p100 fragment containing ankyrin, which generates negative feedback on the main NF-kB signaling. 101 , 102 …”
Section: Nf-kb Secondary Activation Pathwaymentioning
confidence: 99%
“…Another example relates to the crosstalk between EGFR and the Hippo/YAP pathway. This pathway is the main route regulating tissue enlargement and organ size, and it is activated in response to cell cycle arrest and downstream signaling to RAS [ 104 ]. Essentially, the Hippo pathway controls a kinase cascade that inactivates Yes-associated protein (YAP), which plays central roles in the progression of cervical cancer.…”
Section: Crosstalk Between Egfr and Other Signaling Pathwaysmentioning
confidence: 99%
“…In addition, we found that TEAD family was influenced on the immune cells. Reports have demonstrated that TEAD could coordinate several signal pathways such as Hippo, EGFR, Wnt and TGFβ [38]. The abnormal expression of TEAD could modulate several cancer-associated genes, including MYC, KRAS, NF2, BRAF and LKB1, which had crucial roles in the regulation of tumor immunity [39].…”
Section: Discussionmentioning
confidence: 99%